Optical Performance of Sodium Tungsten Bronze Particles in Transparent Matrix: An Ensemble Particle Modeling Study - Hao Tu; Da-Ren Chen (Aerosol and Air Quality Research)
Abstract Different from published works via single particle modeling, the optical performance of multiple sodium tungsten bronze particles (a near-infrared shielding and visible light transparent material) in a transparent matrix was modeled in this study. The effects of particle size, concentration, and shape on the optical performance of particles were investigated. Our particle ensemble modeling showed that multiple light scattering among particles dramatically increased the chance of near-infrared light absorption in a particle-suspended matrix, which differs from that observed in a single particle modeling. The ensemble and single particle modelings evidenced the increase of near-infrared shielding (extinction) with the increase of particle size. For the particle ensemble at a fixed mass concentration, a favored particle size existed for shielding the maximal near-infrared light. It was also found that the attenuation coefficient (normalized by the mass concentration) varied with the mass concentration of particles. The above variation was dependent on the particle size. The near-infrared shielding performance can be improved by cubic-shaped particles due to the localized surface plasmon resonance (LSPR) occurred at the particle corners and edges.